Development of Cordierite Ceramic Cookware - T.saengchantara, Wanna; Punsukmtana, Lada; Junlar, Pranee (Bulletin of Applied Sciences, 2022)
This study is to develop cordierite ceramic cookware by synthesis of cordierite body using kaolin, ball clay, talc, and alumina at sintering temperature 1300 °C. The synthetic cordierite could withstand the thermal shock up to 400 °C and had the coefficient of thermal expansion of 3.09x10-6/°C. The lower coefficient of thermal expansion glaze, 2.61x10-6/°C, was also developed for the synthetic body. After, the crazing resistance test by autoclave at 250 psi, the glaze did not craze. Then the 7 inch diameter pots were prepared and used for the cooking test on a gas stove-top or hot plate for more than 50 cycles. The results showed that the pots were crack free.